PENERAPAN SISTEM FILTRASI AIR BERBASIS ENERGI SURYA TERINTEGRASI DENGAN PEMBERDAYAAN MASYARAKAT UNTUK PEMULIHAN LAYANAN DASAR PASCABENCANA DI DESA BABO, ACEH TAMIANG - Defry Basrin; Zainal Arif; Muhammad Amin; Al Amin; Marendra Rizky; Arifin Ihsan Hasibuan; Hafiz Hidayat; Sari Yuliani; Fauzia Hanum; Naura Ananda Rizal; Siti Sarah; Chairul Nisa; Nazwa Amalia; Fadhilah Maharani Putri Rambe; Lukman Nul Hakim (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
This community service program was conducted in Babo Village, Aceh Tamiang District, an area affected by flash flooding, with major problems including limited access to clean water, damaged infrastructure, low utilization of renewable energy, and limited community capacity for environmental management. The program aimed to improve basic services and strengthen community capacity by implementing a solar-powered water filtration system in combination with a community empowerment approach. The method was carried out using a participatory approach through several stages, including socialization, training, technology implementation, mentoring, and evaluation. The results showed improvements in clean water access from approximately 20% to 80%, in energy utilization from 10% to 75%, and in community participation from 40% to 70–80%. The program improved basic service quality, environmental awareness, and community independence. Overall, the activity demonstrated positive impacts and has strong potential for sustainable post-disaster recovery based on community empowerment.